2009
DOI: 10.1002/jat.1489
|View full text |Cite
|
Sign up to set email alerts
|

Post‐partum testosterone administration does not reverse the effects of perinatal exposure to cadmium on rat offspring development

Abstract: This study investigated the effects of perinatal cadmium exposure on physical and reflexologic development of pup rats. It was examined if the immediate postpartum testosterone administration was able to reverse the toxic effects of the metal. Forty Wistar pregnant rats were divided into three groups: control and 10 and 20 mg kg(-1) per day of cadmium chloride. These dams were treated from gestational days 18 to 21, and until the 7th lactation day. Immediately after birth, half of the offspring from the experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Cadmium can cause severe toxicity in rodents, including changes in development and even mortality (Li and Lim, ; Waalkes and Rehm, ; Couto‐Moraes et al , ). Similar results were obtained here and the highest dose of Cd caused mortality and a reduction in body weight gain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cadmium can cause severe toxicity in rodents, including changes in development and even mortality (Li and Lim, ; Waalkes and Rehm, ; Couto‐Moraes et al , ). Similar results were obtained here and the highest dose of Cd caused mortality and a reduction in body weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…On account of its large‐scale industrial use (Page et al , ), cadmium (Cd) is a widespread pollutant in the environment (World Health Organization, ). Cd poisoning is harmful to human and animal tissues and the liver represents an important target for Cd accumulation in the body (Frazier and Puglese, 1978; Couto‐Moraes et al , ). Cd hepatotoxicity can be associated with an over‐production of reactive oxygen species (ROS) (Eaton et al , ; Goering et al , ), lipid peroxidation (Manca et al , ; Muller, ), carcinogenesis (Waalkes and Rehm, ) and modification of the expression of proteins (Beyersmann and Hechtenberg, ).…”
Section: Introductionmentioning
confidence: 99%
“…There has been emerging evidence that Cd, together with other environmental stressors, could be associated with increased incidences of a number of chronic and malignant diseases (reviewed in: Godt et al ., ; Järup, ; Nordberg et al ., ; Satarug et al ., ). Recent literature data refer to several developmental windows during which maternally mediated exposure to Cd took place and promoted changes in sexual development and steroidogenesis in the offspring (Couto‐Moraes et al ., ; Ji et al ., ; Salvatori et al ., ). As the placenta deters most of the Cd, the impairments of gonadal steroidogenesis due to maternal exposure in late pregnancy are not caused by direct action of Cd on foetal gonads.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Li et al (2011) found that TP has no effects on the testicular and epididymis coefficient in juvenile male rats or on the pregnancy rate and embryo numbers in adult female rats. Testosterone administration is not able to reverse the toxic effects of cadmium, even those parameters directly relates to the androgenic system such as the testis descent and anogenital distance delays (Couto-Moraes et al, 2010). The above studies showed that the effects of TP/testosterone on reproductive system are closely correlated with the dosage.…”
Section: Introductionmentioning
confidence: 88%